Integrative proteomic and physiological analyses of the molecular response to dessication-stress in Auricularia fibrillifera - Guo, Hao; Xiong, Xingwei; Wang, Yiqin; Tian, Huaizhi; Zhang, Suqin; Geng, Guangdong (Frontiers in Plant Science, 2022)
Drought stress is one of the main factors influencing the growth and development of an organism. Auricularia fibrillifera has strong dessication resistance. In A. fibrillifera under dessication-stress, the melanin content of fruiting bodies elevated significantly by >10-fold compared with the control. Folate content also increased sharply but decreased significantly after rehydration, and amino acid and biotin levels increased by 40.11% and 22.14%, respectively. In proteomic analysis, 1,572 and 21 differentially abundant proteins (DAPs) were identified under dessication-stress and rehydration, respectively. A large number of DAPs were annotated in “amino acid metabolism,” “carbohydrate metabolism,” and “translation” pathways, and the DAPs related to osmotic regulation and antioxidant enzymes were significantly increased in abundance. Transcriptome-proteome association analysis showed that most DAPs (30) were annotated in the “biosynthesis of antibiotics” pathway. DAPs and corresponding differentially expressed genes were all up-regulated in the “biotin biosynthesis” pathway and associated with “folate biosynthesis” and “phenylalanine, tyrosine, and tryptophan biosynthesis.” In the analysis of protein–protein interactions, the DAPs annotated in the “phenylalanine, tyrosine, and tryptophan biosynthesis” pathway had the strongest interactions with other DAPs. These enriched pathways could enhance amino acid, folate, biotin, and melanin levels during desiccation stress, which is consistent with the physiological data (amino acid, folate, biotin, and melanin contents). In addition, many DAPs related to the cytoskeleton were significantly increased in abundance under dessication-stress. Physiological and transcriptome data were in agreement with proteomic results. This work provides valuable insight into the dessication-tolerant mechanisms of A. fibrillifera.